Outcome of ultrasound guided percutaneous needle aspiration versus conventional incision and drainage in the management of small breast abscess (Journal of the Medical College for Women & Hospital, 2026)
Background: Breast abscesses, are a very common clinical entity identified in daily practice. At an initial presentation it may be treated conservatively with antibiotics. Minimal invasive surgery is replacing the traditional management. Aim: To compare the outcome and effectiveness of ultrasound guided percutaneous needle aspiration with conventional incision and drainage in management of small breast abscess. Methodes: This Quasi-experimental study was conducted in the Department of Surgery, Sir Salimullah Medical College Mitford Hospital, Dhaka from July 2023 to June 2024. A total 50 female patients with the diagnosis of breast abscess were included according to selection criteria and then divided into 2 groups by alternative consecutive manner (Group-A and Group-B). After proper evaluation, informed written consent was obtained. In group A, patients were treated by ultrasound guided percutaneous aspiration with 19G needle under local anesthesia. In group-B, patients were treated by conventional incision and drainage under general anesthesia. Data was sorted and analyzed by SPSS 26 version. Independent sample t test and Chi-Square test were performed as applicable. Results: In this study, mean duration of procedure was 15.64±3.33 min in group A and 31.48±7.05 min in group B. VAS score was 2.72 ± 1.28 in group A and 5.28 ± 1.28 in group B. The time required for the procedure and VAS score in Group A were significantly (p